Efektivitas Dwelling Time di Terminal Petikemas Pelabuhan Soekarno Hatta Makassar - Haerany, Henny; Shauqy, M. Azhar (Universitas Negeri Makassar, 2021)
An important issue in transportation planning is the technological response to the growing demand for transportation services. Today the world's attention in the field of transportation is focused on container technology because of the high loading and unloading speed. Another advantage of container technology is that the damage and loss of payloads is very small, and with the use of containers the function of the warehouse can be eliminated requiring only a wide open field. The purpose of this study was to analyze the performance of CC, RTG, and HT tools in TPM, analyze the working time of the tools in the container terminal, and formulate effective scenarios of container dwelling time in TPM. The results showed that the best proposed scenario in handling loading and unloading in container terminals is scenario 1 based on the average total time of container handling cycle both in the loading and unloading process. The time difference in the initial condition and the result of scenario 1 simulation is 14 minutes. As for the loading process of 3 minutes. From the simulation results, with the selection of scenario 1 as the best scenario for TPM, with a lower average cycle time then this can be one of the efforts to reduce dwelling time for the handling system.Â Keywords: transportation; container port; dwelling time